Seizures rapidly impair phosphorylation-dependent regulatory mechanisms of KCC2. - Silayeva, Liliya. (2017)
Abstract: Status epilepticus, the development of prolonged or repetitive epileptiform activity without recovery in between, is a medical emergency. The vast majority of biomedical research applied to SE treatment has focused on targeting the GABAA receptor to promote neuronal inhibition. Little attention is given to the mechanism that establishes hyperpolarizing GABAA receptor currents in the adult brain. The K+-Cl- cotransporter KCC2 has been well established as the primary chloride extrusion mechanism in adult neurons that generates the low intracellular Cl- concentration necessary for fast synaptic inhibition. The major findings of this study are 1) phosphorylation of KCC2 at S940 is necessary for surviving kainate-induced SE, 2) phosphorylation of KCC2 at T906 contributes to the behavioral and electrographic seizures observed upon SE induction, and 3) phosphorylation of KCC2 at T906 may be mediated by Wnk3 kinase. These findings improve our understanding of the mechanisms underlying the development SE, which could in turn lead to novel therapeutic strategies for the treatment of this debilitating and deadly condition.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Neuroscience.; Advisors: Stephen Moss, and Jamie Maguire.; Committee: Chris Dulla, Dan Co, and Kristopher Kahle.; Keyword: Neurosciences.